Shelf Life of Breadfruit (Artocarpus altilis (park) Fosberg) - Chitra K Pillai (Department of Processing Technology, College of Horticulture, 2001)
An experiment was conducted in the Department of Processing Technology, College of Horticulture, Vellanikkara during 2000-01 to evolve a simple and cheap technique for storage of fresh breadfruit under ambient and refrigerated conditions and to store it in minimally processed and dehydrated forms for making it available during the off season. Packaging fresh fruits in unventilated PE pouches as well as wrapping of individual fruits with cling film proved to be beneficial in extending the life up to five days at ambient and for nine days at refrigerated conditions with least deteriorative changes. Modified atmosphere packaging proved to be beneficial in extending the life of minimally processed breadfruit slices, when coupled with low temperature ( storage it was even more successful in extending he life as well as quality of the product. The breadfruit 'pieces dehydrated after pre-treating with citric acid + KMS showed better oolour, lesser shrinkage and higher reconstitution and could be stored for four months without any spoilage, when packed in PP or PE bags after subjecting it to microwave oven drying.